Поселення малобудківського типу біля с. Тимченки у басейні р. Сіверський Донець - Буйнов, Ю.В. (Археологія, 2006)
Статтю присвячено публікації матеріалів, здобутих під час розкопок поселення з речами малобудківського типу біля с. Тимченки Харківської обл. Особливу увагу приділено питанням хронології та культурної належності цієї пам’ятки. Для решения вопросов о хронологии и периодизации бондарихинской культуры особое значение имеют памятники с четкой стратиграфией. один из них — поселение у с. Тимченки Змиевского р-на Харьковской обл., в мысовой части которого (раскоп 5) удалось зафиксировать последовательное залегание отложений с керамикой малобудковского и классического бондарихинского типов. Материалы из культурного слоя и жилища позволяют датировать малобудковский комплекс временем не ранее ХІІ в. до н. э. и рассматривать его в качестве составной части раннего периода бондарихинской культуры. Monuments with distinct stratigraphy are especially important in solving the problem of chronology and periodization of the Bondarykhinsk culture. one of such is a settlement studied by the authors of the present article near the village of Tymchenky in Zmievskyj Region of Kharkiv oblast. Its promontory part (excavation trench 5) revealed sequential deposition of sediment containing ceramics of Malobudkivsk and classical Bondarykhinsk types. Materials from the archaeological layer and from the dwelling permit dating the Malobudkivsk assemblage from not earlier than the 12th c. BС and considering it as a constituent part of the earlier in the Bondarykhinsk culture.